Total Phenolic Contents and Anti-lipooxygenase Activity of the Methanolic Extracts from Durio zibethinus Murr (Journal of Scientific Research, 2022)
Durio zibethinus parts (leaves, stem bark, and root) used to treat malaria fever, vermifuge, diabetes, jaundice, inflammation, and oxidative stress management prompted the investigation of their total phenolic contents and anti-lipooxygenase activities. The total phenolic concentration of D. zibethinus parts was determined spectrophotometrically after collection and extraction. The anti-inflammatory activity was estimated using a lipooxygenase assay. Total phenolic content measured in gallic acid equivalent (GAE) gave the highest levels of 6.88 ± 1.54, 23.32 ± 1.73, and 29.00 ± 3.43 mg GAE/g sample weight leaves stem bark, and root extracts, respectively. The plant extracts showed lower anti- lipooxygenase activity in leaves (IC50 µg/mL- 1.464) and stem bark (IC50 µg/mL- 1.203), but had significant activity in root (IC50 µg/mL- 1.400) compared to standard indomethacin (IC50 µg/mL- 1.660). The plant extract's declining order of anti- lipooxygenase activity follows the same trend with the phenolic contents, indicating that the extract's magnitude of anti- lipooxygenase activity is comparable with the quantity of phenolic compounds present in the extracts. Hence, the D. zibethinus extracts are a potential candidate for a plant-derived anti-inflammatory agent.